Evaluation of perceived stress and coronavirus-specific anxiety among hospitalized COVID-19 patients – A cross-sectional study - Arul Varman, P; Ananthi, P; Sugirda, P (Asian Journal of Medical Sciences, 2022)
Background: COVID-19 pandemic enmeshed all people across the globe in myriad of problems and adversely affected their physical and mental health. Among all, patients who had been infected with COVID-19 might be at higher risk of psychological distress for obvious reasons. Aims and Objectives: The aim of the study was to find out the prevalence and level of perceived stress and coronavirus-specific anxiety in patients affected by COVID-19. Materials and Methods: This cross-sectional study was conducted on in-patients of a COVID-19 designated hospital who were about to get discharged. After screening the eligible patients with GHQ-12, patients who gave consent were interviewed with perceived stress scale (PSS)-4 and coronavirus anxiety scale. Results: Mean age of the study population was 41 years and majority (54.4%) belonged to 40–60 years of age. Slight preponderance of females (54.1%) noted and17.4% lost their source of income and encountered acute financial crisis. Mean duration of stay in the hospital was 10.2 (±4.4) days. Mean perceived stress and coronavirus-specific anxiety were 9.6 (±2.2) and 10.39 (±3.1), respectively. Loss of a family member due to COVID-19 infection, active COVID-19 infection in any family member, poor social support, and financial crisis were the factors correlated with higher PSS scores. Conclusion: Psychosocial factors contributed significantly for the higher level of perceived stress in COVID-19 patients in our study.